Determinant of Consumer’s Decision to Use Islamic Saving Account in Bank Syariah Indonesia Post Merger in 2021 Period - Apriliana Ika Kusumanisita; Raditya Iqbal Anugrah; Muchammad Taufiq Affandi (Al Tijarah, 2023)
Increasing awareness about halal products  in the Islamic finance industry sector can encourage the development of Islamic economy and finance in Indonesia. The financial industry is a pillar of the national economy that is expected to advance the general welfare and global competitiveness, especially in Islamic banking which has contributed to economic growth in Indonesia. Theory of Planned Behaviour (TPB) is used to measure customers decision to keep saving in Bank Syariah Indonesia. The independent variables used in the study were trust, quality of service, religiosity, and Revenue Sharing, while the dependent variables used in the study were customer decisions to keep saving. The sample of this study was 120 respondents from Customers of Bank Syariah Indonesia located throughout Java Island. The results showed that Trust, Quality of Service, and Religiosity had no significant effect on the customer's decision to keep saving in Bank Syariah Indonesia, meanwhile revenue sharing has a significant influence on the decision of customers to keep saving in Bank Syariah Indonesia.